PENINGKATAN PEMAHAMAN KONSEP JARING-JARING MAKANAN MELALUI MODEL COOPERATIVE LEARNING KELAS V DI SDN RANCAMAYA 2 - Rizka Juniarti Pratiwi; Hendro Prasetyono (STKIP Subang, 2025)
This classroom action research aims to improve students’ understanding of the food web concept through the application of the cooperative learning model at SDN Rancamaya 2. Before implementing the model, about 40% of the 30 students could not understand the concept properly. After applying the cooperative learning approach, approximately 95% of students achieved conceptual mastery. The study employed two cycles based on the Kemmis and McTaggart model, including stages of planning, action, observation, and reflection. Data were collected using pretests, posttests, observation sheets, and student interviews. The findings showed a significant increase in students’ conceptual understanding and active participation. The results highlight that cooperative learning fosters collaboration, peer teaching, and engagement, which are critical for science learning under the Merdeka Curriculum. The research concludes that the cooperative learning model effectively enhances comprehension of food webs and recommends further implementation of structured group-based activities in elementary science classrooms. .